2003
DOI: 10.1016/s0040-5809(03)00012-1
|View full text |Cite
|
Sign up to set email alerts
|

Optimal foraging and predator–prey dynamics III

Abstract: In the previous two articles (Theor. Popul. Biol. 49 (1996) 265-290; 55 (1999) 111-126), the population dynamics resulting from a two-prey-one-predator system with adaptive predators was studied. In these articles, predators followed the predictions of optimal foraging theory. Analysis of that system was hindered by the incorporation of the logistic description of prey growth. In particular, because prey self-regulation dependence is a strong stabilizing mechanism, the effects of optimal foraging could not be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 11 publications
2
31
0
1
Order By: Relevance
“…1, panel a). This positive effect of adaptive foraging on diversity is suggested by theoretical works (Krivan 2003; Krivan & Eisner 2003) and observed in data from several experiments (reviewed in Bolker et al. 2003).…”
Section: Structural and Functional Consequences Of Adaptive Foragingsupporting
confidence: 55%
See 1 more Smart Citation
“…1, panel a). This positive effect of adaptive foraging on diversity is suggested by theoretical works (Krivan 2003; Krivan & Eisner 2003) and observed in data from several experiments (reviewed in Bolker et al. 2003).…”
Section: Structural and Functional Consequences Of Adaptive Foragingsupporting
confidence: 55%
“…1, panel a). This positive effect of adaptive foraging on diversity is suggested by theoretical works (Krivan 2003;Krivan & Eisner 2003) and observed in data from several experiments (reviewed in Bolker et al 2003). As diversity partly determines the degree of complexity of the community, this establishes a clear link between adaptive foraging and food web size.…”
Section: Effects Of Optimal Foraging On Stability and Co-existencementioning
confidence: 59%
“…Mixed results have been obtained on the prey selection of pumas: While two studies concluded that pumas select for fawns of white-tailed deer ( Odocoileus virginianus ) and mule deer ( Odocoileus hemionus ) [18] [85], others found selection for adult mule deer [7]. Our results show that lynx kill a significant proportion of adults, in particular prime-age animals, which can have a strong impact on recruitment and population size of the prey population [86]. However, the observed selection for males is expected to reduce this impact [3].…”
Section: Discussionmentioning
confidence: 80%
“…Predation plays a key role in shaping animal populations and communities through predator arrival timing, prey killed, and through the behavioural and life history decisions of both predators and prey (Lima and Dill 1990;Fryxell and Lundberg 1994;Olito and Fukami 2009). Predators can affect prey demography both through predation-associated mortality (direct effects; Krivan and Eisner 2003) and through the costs of anti-predator behavioural and physiological responses (indirect effects; Creel and Christianson 2008). The direct effects of predation on prey population dynamics can be dramatic (Sinclair et al 2003;Wittmer et al 2005); in contrast, the indirect effects of predation on prey population dynamics are generally less obvious.…”
Section: Introductionmentioning
confidence: 99%